Noggin Nodding: Head Movement Correlates With Increased Effort in Accelerating Speech Production Tasks - Tiede, Mark; Mooshammer, Christine; Goldstein, Louis (Frontiers in Psychology, 2019)
Movements of the head and speech articulators have been observed in tandem during an alternating word pair production task driven by an accelerating rate metronome. Word pairs contrasted either onset or coda dissimilarity with same word controls. Results show that as production effort increased, so did speaker head nodding, and that nodding increased abruptly following errors. More errors occurred under faster production rates, and in coda rather than onset alternations. The greatest entrainment between head and articulators was observed at the fastest rate under coda alternation. Neither jaw coupling nor imposed prosodic stress was observed to be a primary driver of head movement. In alternating pairs, nodding frequency tracked the slower alternation rate rather than the syllable rate, interpreted as recruitment of additional degrees of freedom to stabilize the alternation pattern under increasing production rate pressure.